Early post-operative relief of pain and shivering using diclofenac suppository versus intravenous pethidine in spinal anesthesia - Ali Janpour Ebrahim; Rabiee Mozaffar; Bani-hashem Nadia; Jabbari Ali (Wolters Kluwer Medknow Publications, 2014)
Background: Pain and shivering are two challenging components in the post operative period. Many drugs were used for prevention and treatment of them. The aim of this study was to compare the effects of prophylactic prescription of diclofenac suppository versus intravenous (IV) pethidine in spinal anesthesia. Materials and Methods: We conducted a multi central, prospective, double-blind, randomized clinical trial on a total of 180 patients who were scheduled for surgery under spinal anesthesia including 60 patients in three groups. Patients were randomly allocated to receive 100 mg sodium diclofenac suppository or 30 mg IV pethidine or placebo. Categorical and continuous variables were analyzed by Chi-square test, t-test, Mann-Whitney and ANOVA or Kruskal-Wallis tests. Results: There was no statistical difference with regard to patient characteristics and hemodynamic indices among the three groups. Nine (15%), 10 (16.65%) and 24 (40%) of patients in diclofenac, pethidine and control groups reported pain and 2, 2, 7 patients received treatment due to it, respectively (P = 0.01). Prevalence of shivering in pethidine group and diclofenac group was the same and both of them were different from the control group (P < 0.001). Pruritus was repetitive in the pethidine group and was statistically significant (P = 0.036) but, post-operative nausea and vomiting was not significantly different among groups. Conclusion: A single dose of sodium diclofenac suppository can provide satisfactory analgesia immediately after surgery and decrease shivering without remarkable complications. This investigation highlights the role of pre-operative administration of a single dose of rectal diclofenac as a sole analgesic for early post-operative period.